ANALYSIS OF MARKETING STRATEGY IN INCREASING THE NUMBER OF STUDENTS - marzuki, marzuki; maulana, olan (Mu'amalatuna: Jurnal Ekonomi Syariah, 2021)
This study plans to dissect the idea of the concept of marketing strategy, what variables support and hinder and how to develop the methodology used at the University of Muhammadiyah Lampung with the aim of increasing the number of new students. This exploration is an illustrative quantitative study, the methods used in collecting information are interviews, observations, documentation and questionnaires. The consequences of various information are examined using the Force Field Analysis method. The idea of a procedure to increase the number of new students at Muhamamdiayah University Lampung with approaches including: Product (product), Price (price), people (human resources), Place (location/place), Promotion (promotion), Physical Evidance (Physical Facilities), Process (Service) has not run ideally. An improvement technique is needed with the ultimate goal of increasing the number of new students at the Muhammadiyah University of Lampung, providing smooth abilities to students, expanding teaching skills for lecturers, not increasing tuition fees, providing innovative abilities to students. Furthermore, to increase the number of new students, a special institution is needed that handles new students who intend to increase the number of new students.